Education Based on Ethnopedagogy in Maintaining and Conserving the Local Wisdom: A Literature Study - Selasih, Ni Nengah; Sudarsana, I Ketut (Jurnal Ilmiah Peuradeun, 2018)
Etnopedagogy plays a role in the values-based education of culture for teaching and learning in the context of teaching as a cultural activity and the culture of teaching. The values ​​of local wisdom as a source of innovation in the field of culture-based education of local communities through social contacts that are educational-pedagogical to the communicant, namely cognitive (know about something), affective (formation attitude), and conative (behavior, act to do something). The process of attitude change takes place through three stages: attention, understanding, acceptance, the influence of social contact depending on the professionalism of the educator, leads to the three processes through communicative learning.The transformation of society in the direction of modern society needs to begin with the understanding that society as a social system in which structural, cultural, and social processes are the factors that cause change of society with the basic view that education takes place in society, with community resources, and for society facing an era of globalization filled with challenges, competition, and uncertainty, it takes a teacher who has a new paradigm, strategy, and learning model that contains the content of life skills based on the concept of broad based education, which implements Renewal-Train Strategy and Learner Centred Strategy.